A non-randomised trial of an art therapy intervention for patients with haematological malignancies to support post-traumatic growth. (July 2013) - Singer, Susanne; Götze, Heide; Buttstädt, Marianne; Ziegler, Corinna; Richter, Robert; Brown, Anna; Niederwieser, Dietger; Dorst, Jana; Jäkel, Nadja; Geue, Kristina
The aim of this study was to determine the effect of art therapy on post-traumatic growth in patients with haematological malignancies in a non-randomised trial ( n = 36, intervention group; n = 129, control group). Art therapy was administered over a period of 22 weeks in small groups. Post-traumatic growth was measured with the Stress-Related Growth Scale. After controlling for the effect of potential confounders, no difference in post-traumatic growth was observed between the intervention and control groups after 22 weeks. There was no evidence for an effect of weekly group sessions with art therapy on post-traumatic growth in patients with haematological malignancies.